Special Protection for Children Victims of Psychological Violence at the Community Empowerment, Women and Child Protection Service of Jambi City. - Kurniadi, Wahyu (Siber International Journal of Advanced Law (SIJAL), 2023)
Violence against children, particularly sexual violence, remains a serious and growing issue in Indonesia. As a vulnerable group, children require strong legal protection to safeguard their rights. Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS) serves as a comprehensive legal framework addressing prevention, victim protection, and law enforcement concerning sexual violence, including cases involving children. This article analyzes the implementation of UU TPKS in tackling child sexual violence, highlighting progress and existing challenges. While the law marks significant advancement, issues such as lack of public awareness, limited support services, and cultural barriers hinder its effectiveness. Strengthened collaboration between the government, law enforcement, and society is essential to ensure optimal child protection.